Recent methods in the production of activated carbon from date palm residues for the adsorption of textile dyes: A review - Alharbi, Hattan A.; Hameed, Bassim H.; Alotaibi, Khaled D.; Al-Oud, Saud S.; Al-Modaihsh, Abdullah S. (Frontiers in Environmental Science, 2022)
Textile dyes are organic compounds that can pose an environmental threat if not properly treated. They can cause many problems ranging from human health, ecosystem disturbances, and the reduction of the esthetic value of water bodies. The adsorption process using activated carbon (AC) has been proven to be effective in treating dyes in wastewater. However, the production of AC is limited by the non-renewables and relatively expensive precursor of coal. Date palm residues (DPRs) provide a good alternative for AC’s precursor due to their continuous supply, availability in a large amount, and having good physiochemical properties such as high oxygen element and fixed carbon. This study provides a review of the potential of date palm residues (DPRs) as AC in adsorbing textile dyes and the recent technological advances adopted by researchers in producing DPR-based AC. This review article focuses solely on DPR and not on other biomass waste. This study presents a background review on date palms, textile dyes, biochar, and AC, followed by production methods of AC. In the literature, DPR was carbonized between 250 and 400°C. The conventional heating process employed an activation temperature of 576.85–900°C for physical activation and a maximum of 800°C for physicochemical activation. Chemical agents used in the chemical activation of DPR included NaOH, KOH, ZnCl2, H3PO4, and CaCl2. The maximum surface area obtained for DPR-AC was 1,092.34 and 950 m2/g for physical and chemical activation, respectively. On the other hand, conditions used in microwave heating were between 540 and 700 W, which resulted in a surface area of 1,123 m2/g. Hydrothermal carbonization (HTC) utilized carbonization temperatures between 150 and 250°C with pressure between 1 and 5 MPa, thus resulting in a surface area between 125.50 and 139.50 m2/g. Isotherm and kinetic models employed in the literature are also discussed, together with the explanation of parameters accompanied by these models. The conversion of DPR into AC was noticed to be more efficient with the advancement of activation methods over the years.